Pengkayaan UML dengan Metoda Formal - Pujianto Yugopuspito (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Unified Modeling Language (UML) is a de-facto object-orieted model standard. Manymodels can be visualized and designed by using UML tool, e.g. Rational Rose. We enrich theUML by means of adding a capability to produce a set of formal specifiation of Z notation.This additonal capability is a part of a studi on formal framework of transformationrelational databases to object-relational databases. The enrichment of UML in formalspecification will give an opportunity to explore UML class diagram in the sense of formalmethods. This approach will enable to use the streght of formal methods within UML.Keywords: class diagram, UML, formal methods, formal specification, Z.